Analysis of the clinical characteristics and neonatal outcomes of seven cases of pregnancy luteoma discovered incidentally at cesarean section - Junhua Shen; Lanlan Tang; Genping Huang; Xiaoxia Bai; Baohua Li; Zhengping Wang (BMJ Publishing Group, 2021)
Objective: In this study, we summarize the clinical characteristics and neonatal outcomes of patients with pregnancy luteomas that were identified incidentally at cesarean section in our hospital. We also provide a review of the existing literature relating to this condition. Methods: A total of seven cases of pregnancy luteoma were enrolled from our hospital into this retrospective study between March 2013 and February 2018. We then evaluated the clinical characteristics and neonatal outcomes of these patients. Results: All seven patients with pregnancy luteomas found incidentally during Cesarean sections at term as a result of obstetric indications. These masses were unilateral and ranged from 2 to 10 cm in size. All patients underwent partial ovariectomies or oophorocystectomy due to presumptive benign ovarian tumors. Two patients had gestational diabetes and one patient had gestational hypertension. One patient developed hirsutism and a deepened voice. Of the seven newborns, three were girls and four were boys. Physical examinations of the newborns were normal and no virilization was detected among the infant girls. Conclusion: Pregnancy luteoma may be more common than expected. Better strategies are now needed to educate obstetricians about the clinical features of pregnancy luteoma so that they can avoid unnecessary surgery.